Exploring sustainable market opportunities for Local Generation's mixed plastic packaging waste - Jayamani, Saravana; Goel, Aastha; Radhakrishnan, Manish Krishnan (2011)
European Union’s 2020 target by 2020 is driving all the member states towards low carbon green economy and UK is in forefront of the change. UK government is using the transition to green economy to tackle economic instability and deficit. To ease the transition, various government departments are working with businesses and supporting them through many grants and funds. Anaerobic digestion (AD) is one such green business that generates energy from food waste that would have been otherwise sent to landfill. A unique challenge in AD is the sustainable way of disposing packaging plastic waste that is generated from the process. Around the world, recycling and reprocessing mixed plastic has been a challenge. Now there are multiple technologies available worldwide to handle this issue.